Biosorption of Nickel (II) from aqueous solution onto activated carbon prepared from chicken feather - E.D. Paul; N.C. Nwokem; F.U. Anumonye (Journal of Applied Sciences and Environmental Management, 2019)
Industrial waste water is a potential threat to human health mainly because of the presence of nonbiodegradable, hazardous heavy metals. This research focuses on the use of Activated Carbon from Chicken Feathers (ACCF) in the removal of Ni (II) ions from aqueous solution. Fourier Transform Infrared (FTIR) analysis was carried out on ACCF to reveal the functional groups present which will aid adsorption. The optimization of factors such as initial metal ion concentration, pH, and contact time were investigated at ambient temperature. The optimum pH, initial metal ion concentration and contact time were therefore determined. The experimental data obtained for Ni2+ sorption were treated using pseudo first order and second order kinetic models. The adsorption behavior was found to follow pseudo second order kinetics. This study demonstrates the effectiveness of ACCF in the removal of Ni (II) ion from aqueous solution.